Tumor-derived extracellular vesicles for the active targeting and effective treatment of colorectal tumors in vivo. (31st December 2022) - Nguyen, Van Du; Kim, Ho Yong; Choi, You Hee; Park, Jong-Oh; Choi, Eunpyo
Abstract: Colorectal cancer remains one of the main causes of cancer-related deaths worldwide. Although numerous nanomedicine formulations have been developed to tackle the disease, their low selectivity still limits effective therapeutic outcomes. In this study, we isolated extracellular vesicles (EVs) from CT26 colorectal cancer cells and 4T1 murine mammary carcinoma cells, loaded them with the chemotherapeutic agent (doxorubicin, DOX). Then we evaluated the cellular uptake of the extracellular vesicles both in 2D monolayer and 3D tumor spheroid setups using confocal laser scanning microscope and flow cytometry. In vivo tumor homing of the extracellular vesicles was verified on CT26 tumor bearing BALB/c mice using in vivo imaging system. Finally, in vivo therapeutic effects were evaluated and compared using the same animal models treated with five doses of EV formulations. CT26-EV-DOX exhibited excellent biocompatibility, a high drug-loading capacity, controlled drug release behavior, and a high capability for targeting colorectal cancer cells. In particular, we verified that CT26-EV-DOX could preferentially be up taken by their parent cells and could effectively target and penetrate 3D tumor spheroids resembling colorectal tumors in vivo in comparison with their 4T1 derived EV partner. Additionally, treatment of colorectal tumor-bearing BALB/c mice with of CT26-EV-DOX significantly inhibited the growth of the tumors during the treatment course. The developed CT26-EV-DOX nanoparticles may present a novel and effective strategy for the treatment of colorectal cancer.